Development of a novel bead display technology to identify protein ligands: application to identification of viral entry inhibitors and T-cell epitopes - Huang, L (2013)
With the continued need for drug discovery and the quest to understand disease and treatment, there remains a requirement for improved methods to study protein-protein interactions and to identify potential drug leads for protein targets. We sought to develop a new approach to directly link genotype and phenotype to use as a probe for the identification of binding partners of proteins. The method creates millions of water-in-oil emulsions, each of which functions as a micro-environment for the amplification of a library of random peptide-encoding DNA molecules, which covalently bind to a bead. Subsequently the emulsions are broken and the bead-DNA complexes are recovered, which subsequently form another emulsion with in vitro transcription and translation components and incubated under suitable protein synthesis conditions. The synthetic peptide is designed with tags that link to the same bead which it is translated from. In chapter 3, the detailed design and optimisation of the method will be discussed. Cross-clade neutralising antibodies specific to HIV-1 are rare, partly because glycosylation restricts access to conserved backbone residues of gp120. In chapter 4, we hypothesized that peptides may have greater access than relatively large antibody structures, and so used our method to display random peptides on beads using a protein domain scaffold. Using a single round of selection, we identified 22 gp120-binding peptides, 4 of which were able to inhibit HIV-1 replication in vitro. One of the inhibitory peptides was found to bind the CCR5/CXCR4-binding site of gp120 and was able to inhibit clade B and C CCR5-tropic isolates of HIV-1. We have identified HIV-1 cross-clade neutralising peptides using a novel in vitro bead display library. Comprehensive antigenic characterization of a T cell population of unknown specificity is challenging. Existing MHC class I expression systems are limited by the practical difficulty of probing cell populations with an MHC class I peptide library and the cross-reactivity of T cells that are able to recognise many variants of an index peptide. We reasoned that a bead-based display high-throughput approach may overcome these challenges. Using emulsion PCR and emulsion in vitro transcription/translation of a random library of peptides conjugated to β-2-microglobulin on beads, we refolded with exogenous wild-type HLA-A*0201 or CD8-null A*0201 (domains 1 and 2 of HLA-A*0201 and domain 3 of Kb with mutated residues 226A/227L). The HLA bead libraries were used to probe HLA-A*0201-restricted T cells with specificity for influenza, CMV and EBV. High-throughput sequencing was used to rank sequences of identified peptides. Compared to pre-selection sequences, we observed significant enrichment for sequences containing HLA-A2 anchors and correct viral fragments for all T cell populations. HLA bead display provides a novel approach to identify the specificity of T cells. In summary, we combine the convenient handling of beads, the homogeneity of micro-environment in emulsion, and next-generation sequencing to create an attractive alternative to identify ligands of protein targets and antigenic peptides.